Clinical outcomes of patients with resected, early-stage ALK-positive lung cancer. (August 2018) - Chaft, Jamie E.; Dagogo-Jack, Ibiayi; Santini, Fernando C.; Eng, Juliana; Yeap, Beow Y.; Izar, Benjamin; Chin, Emily; Jones, David R.; Kris, Mark G.; Shaw, Alice T.; Gainor, Justin F.
Highlights: One-third of resected ALK -, KRAS- or EGFR- positive lung cancer patients relapsed within 5 years. ALK -positive patients had a numerically shorter relapse-free survival than other groups. Relapse-free survival was not statistically different when molecular subgroups were compared. There was no statistical difference in overall survival across molecular groups. Abstract: Objectives: Reports of the prognostic significance of ALK -rearrangement in resected non-small cell lung cancer (NSCLC) have been contradictory. We aimed to determine the prognosis of early-stage ALK -positive lung cancers relative to KRAS - and EGFR -mutant lung cancers. Material and methods: We reviewed medical records of patients with resected NSCLC harboring an ALK rearrangement (n = 29) or a driver mutation in EGFR (n = 255) or KRAS (n = 480). Recurrence-free survival (RFS) was estimated for each genotype with the differences reported as a hazard ratio (HR). Results: Among the 764 patients, 555 (73%), 101 (13%), and 108 (14%) had stage I, II, and III NSCLC, respectively. ALK -positive patients were distributed across all stages: 10 (34%) stage I, 6 (21%) stage II, and 13 (45%) stage III. Median RFS was not reached for EGFR -mutant patients, 24.3 months (95%CI 11.4–65.3) for ALK -positive patients, and 72.9 months (95%CI 59.7 to undefined) for KRAS -mutant patients. When adjusted for stage, ALK -positive NSCLC remained associated with worse RFS compared to EGFR -mutant (HR 1.8, 95%CI: 1.1-3.1), but not when compared to KRAS -mutant (HR 1.3, 95%CI: 0.8-2.1) NSCLC. Conclusions: In this large series of resected NSCLC, ALK rearrangements were associated with a trend toward inferior disease outcomes compared to other clinically relevant genomic subsets. These data support the need for clinical trials evaluating use of ALK inhibitors among ALK -positive patients with localized or locally-advanced disease.